The Effect of Jarimatika Method Using Papet Media on Learning Outcomes of 4th Grade Elementary School Students Multiplication - Alfina Shofiyana Damayanti; Erna Zumrotun; Wulan Sutriyani (Jurnal Pendidikan Matematika (JPM), 2024)
One of the reasons why the multiplication learning outcomes of grade 4 students at SD Negeri 03 Kedungleper are low is because the students' understanding of the multiplication material is poor. This research aims to determine the relationship between the use of the Jarimatika method using papet media before and after, as well as how much influence this method has on the learning outcomes of grade 4 elementary school students. This research is quantitative research that uses an experimental approach with a one-group pretest-posttest design. The place where this research was conducted was SD Negeri 03 Kedungleper. The research population was grade 4 students, and the sample was 19 grade 4 students. Data collection techniques included observation, tests, and documentation techniques. From the results of the t-test analysis, it can be seen that the use of the Jarimatika method with papet media has a significant influence on the multiplication learning outcomes of grade 4 students at SD Negeri 03 Kedungleper. The calculated t value of 8.732 is greater than the t table value of 1.734, indicating that there is a very significant influence. It has been proven to be an appropriate learning method to help students master multiplication material, as evidenced by student learning outcomes which have increased by 40%. Before this method was used, the average student pretest score was 49.79. After this method was implemented, the average post-test score increased to 80.42. This 40% increase means that students show significant improvement in mastering multiplication material after using the Jarimatika method with paper media, compared to the previous teaching method.